Job Satisfaction and Organizational Citizenship Behavior (OCB) to Achieve Job Performance From the Person Environmental Fit Theory - Dewantara, Yuni Putri (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The match between a person’s characteristics and the environment is referred to as Person Environmental Fit. This study aims to analyze the increase in job performance through job satisfaction and OCB in terms of PE Fit theory. In writing this article using the literature review method. Employee performance is important to improve in order to maintain the company’s position in the increasingly fierce competition. Increased job satisfaction and OCB behavior affect employee performance. Job satisfaction and OCB have a strong influence on the theory of person environmental fit, where when a person feels fit with his environment either partially or completely, job satisfaction and OCB will arise.